Експедиція науковців переяславського та київського скансенів на Чернігівщину у жовтні 1969 року: мета та результати (до 50-річчя Музею народної архітектури та побуту України) - Жам, О. (Краєзнавство, 2019)
У статті досліджуються обставити організації й проведення першої спільної експедиції науковців Державного музею народної архітектури та побуту Української РСР та Переяслав-Хмельницького державного історичного музею на Чернігівщину в жовтні 1969 р. під керівництвом М.І. Жама. Приділена увага передісторії, географії, тематиці, результатам експедиції. This article describes the circumstances of the organization and making the first common scientific exploratory expedition of scientists of The National Museum of Folk Architecture and Everyday life of the Ukraine SSR and Pereyaslav-Khmelnitskiy National Historical Museum at Chernigiv region since October 1-10 1969, under of the head of Pereyaslav Scansen mr. Zham. The primary task of the expedition was to survey the region in order to identify the monuments of folk architecture and collecting items of museum value (household utensils, folk art, crafts, tools) for the Kyiv Scansen. The previous agreement was reached at the meeting, where the question of the ethnographic museums of open air creation was discussed on March 15-18, 1968. There are many members of expedition: M.Zham,O.Iuzvikova, V.Iuzvikov, T.Kozachkovska, V.Shablevsiy, L.Kuzmenko, S.Smolinskiy, I.Zmorovich, V.Melikhova, G.Bandurenko, L.Kolinko. As a result of the search, more than 500 items of the museum value were collected, more of them were handed over to the museum in Kiev, and the unique windmill of the beginning of XIX cent. at the Liska Menskiy district. It was not the last windmill founded in Galitsa village. As a result, members of this expedition identified and inspected a big number of valuable monuments of folk architecture, collected a lot of household items, tools, crafts, works of art, etc. But the main success of expedition was the experience of organization of regional search expedition, a comprehensive study of the ethnic culture of the ethno-region. This expedition has become the impetus for further research of Chernihiv Polissya, activated the scientific expeditionary and searching work in both museums.